The Relationship of White Matter Hyperintensities with Depressive Symptoms and Daily Living Activities in Early-Stage Alzheimer’s Disease Patients - BİLGİÇ, Başar (Noro Psikiyatr Ars, 2013)
INTRODUCTION: Cerebral white matter hyperintensities (WMHs) detected on magnetic resonance imaging scans are frequently seen in both Alzheimer’s disease (AD) and depression patients and believed to play an important role in cognition and mood. Depressive symptoms and depression may accompany AD in all stages of the disease. The aim of the study was to evaluate the relationship of regional WMHs with depressive symptoms, cognitive status, medial temporal lobe atrophy, and daily living activities in early-stage AD patients. METHOD: Forty-five patients with very mild or mild AD were examined. All subjects underwent MRI and were assessed by the Geriatric Depression Scale (GDS) and the Addenbrooke’s Cognitive Examination-Revised (ACE-R) for the evaluation of depressive symptom severity and cognitive status, respectively. The patients were divided into two groups based on the selected cut-off point in the GDS. CDR sum of the boxes (CDR-sb) scores were calculated as a measure of activities of daily living (ADLs). MRI T2-FLAIR slices were used to rate the white-matter lesions according to the Age-Related White Matter Changes Rating Scale, assessing the WMHs in frontal, parietooccipital, temporal, infratentorial and basal ganglia areas individually. Medial temporal lobe atrophy was assessed with high-resolution T1 images using visual rating scale. RESULTS: In the depressive group, frontal WMH scores were found to be higher than in the non-depressive group (p=0.006). ACE-r, CDR-sb and medial temporal lobe atrophy scores did not differ among the groups. CDR-sb scores showed a significant correlation with frontal WMH scores (left frontal WMH r=0.439, p=0.003, right frontal AMH r=0.459, p=0.001). Linear regression models revealed the effect of WMHs on depressive symptoms among the other factors including age, functionality and atrophy in the medial temporal areas. DISCUSSION: Our findings underscore the potential role of regional, particularly frontal AMHs in depressive symptoms and functionality of the early AD patients.